2005
DOI: 10.1103/physrevc.71.044319
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-nucleus reactions and muon capture inC12

Abstract: The neutrino-nucleus cross section and the muon capture rate are discussed within a simple formalism which facilitates the nuclear structure calculations. The corresponding formulae only depend on four types of nuclear matrix elements, which are currently used in the nuclear beta decay. We have also considered the non-locality effects arising from the velocity-dependent terms in the hadronic current. We show that for both observables in 12 C the higher order relativistic corrections are of the order of ∼ 5% on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(127 citation statements)
references
References 40 publications
4
123
0
Order By: Relevance
“…energies and pairing strengths v pair s (p), and v pair s (n) were varied in a χ 2 search to account for the experimental spectra of odd-mass nuclei 11 C, 11 B, 13 C, and 13 N, as explained in Ref. [6]. This method, however, is not applicable for the space S 6 which comprises 21 s.p.…”
Section: Nuclear Structurementioning
confidence: 99%
See 3 more Smart Citations
“…energies and pairing strengths v pair s (p), and v pair s (n) were varied in a χ 2 search to account for the experimental spectra of odd-mass nuclei 11 C, 11 B, 13 C, and 13 N, as explained in Ref. [6]. This method, however, is not applicable for the space S 6 which comprises 21 s.p.…”
Section: Nuclear Structurementioning
confidence: 99%
“…(2.3)], and for the hadronic current operator J α ≡ {J, iJ / 0 } we use the nonrelativistic form. In spherical coordinates (m = −1, 0, +1), and when k is taken to be along the z axis, it reads [6,7] …”
Section: Neutrino (Antineutrino)-nucleus Cross Sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in turn, can be circumvented through the particle-number projection procedure [21,22], i.e., in the framework of the projected BCS (PBCS) approximation. In fact, recently it has been found [23,24] that the low-lying energy spectra in 13 C can be described quite well in the context of the PBCS approximation for the pairing force among the valence neutrons. Moreover, in this study it was shown that the projection procedure is very important to account for the weak decay observables around 12 C.…”
Section: Introductionmentioning
confidence: 99%